2022
DOI: 10.3389/fimmu.2022.861681
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreserved PM21-Particle-Expanded Natural Killer Cells Maintain Cytotoxicity and Effector Functions In Vitro and In Vivo

Abstract: There is a great interest in developing natural killer (NK) cells as adoptive cancer immunotherapy. For off-the-shelf approaches and to conduct multicenter clinical trials, cryopreserved NK cells are the preferred product. However, recent studies reported that cryopreservation of NK cells results in loss of cell motility and, as a consequence, cytotoxicity which limits the clinical utility of such products. This study assessed the impact of cryopreservation on the recovery and function of PM21-particle expande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Use of DMSO as a cryopreservation agent especially for infusible therapeutic cell preservation presents problems: Even though the immediate post-thaw viability of NK cells is generally reported to be quite high (albeit with some cell loss), a drastic decrease in cytotoxicity (down to 10–25% of the fresh cells) post-thaw is very common. Furthermore, in vivo persistence of frozen–thawed NK cells is also reported to be orders of magnitude lower than fresh cells . The main reason for cytotoxicity loss is ascribed to the loss of motility, and significant changes in NK cell phenotype specifically decrease in the cytotoxic CD16+ populations. ,, To resolve the issues associated with cell number and cytotoxicity loss, therapeutic cells need to be expanded for 3–7 days post-thaw to increase cell numbers and activated through interleukin stimulation for a minimum of 12–16 h to recover cytotoxic capability. , Extra processing was required in the clinic, and the need for additional quality control/lot testing requirements increases costs, delays the treatment, and also increases the risk for contamination during expansion of the cells. Another problem with the use of DMSO in cryopreservation formulations is the patient morbidity risk, , requiring the infusion rates to be slowed and sometimes distributed over multiple sessions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of DMSO as a cryopreservation agent especially for infusible therapeutic cell preservation presents problems: Even though the immediate post-thaw viability of NK cells is generally reported to be quite high (albeit with some cell loss), a drastic decrease in cytotoxicity (down to 10–25% of the fresh cells) post-thaw is very common. Furthermore, in vivo persistence of frozen–thawed NK cells is also reported to be orders of magnitude lower than fresh cells . The main reason for cytotoxicity loss is ascribed to the loss of motility, and significant changes in NK cell phenotype specifically decrease in the cytotoxic CD16+ populations. ,, To resolve the issues associated with cell number and cytotoxicity loss, therapeutic cells need to be expanded for 3–7 days post-thaw to increase cell numbers and activated through interleukin stimulation for a minimum of 12–16 h to recover cytotoxic capability. , Extra processing was required in the clinic, and the need for additional quality control/lot testing requirements increases costs, delays the treatment, and also increases the risk for contamination during expansion of the cells. Another problem with the use of DMSO in cryopreservation formulations is the patient morbidity risk, , requiring the infusion rates to be slowed and sometimes distributed over multiple sessions.…”
Section: Resultsmentioning
confidence: 99%
“…18,20,72 To resolve the issues associated with cell number and cytotoxicity loss, therapeutic cells need to be expanded for 3−7 days postthaw to increase cell numbers and activated through interleukin stimulation for a minimum of 12−16 h to recover cytotoxic capability. 19,21 Extra processing was required in the clinic, and the need for additional quality control/lot testing requirements increases costs, delays the treatment, and also increases the risk for contamination during expansion of the cells. Another problem with the use of DMSO in cryopreservation formulations is the patient morbidity risk, 73,74 requiring the infusion rates to be slowed and sometimes distributed over multiple sessions.…”
Section: Thermodynamic and Kinetic Transitions Of Agarosementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, NK cells were better clustered by DeepIFC when fresh sample data was included in training. It has been found that NK cells may not preserve viability and may lose cytotoxicity after the freeze–thaw process [29]. This effect may be reflected in the loss of distinct NK cell morphology, leading to poor predictive performance in frozen samples.…”
Section: Discussionmentioning
confidence: 99%
“…These protocols have unveiled the importance of cytokines such as IL-2 or IL-15 to the post-thaw stimulation of NK cells, 7−9 the possibility of precomplexing engager antibodies to retain NK cell postthaw activity, 10 and the potential of using IL-21-expressing vesicles to expand and freeze NK cells. 11 DMSO has been the cryoprotective agent (CPA) of choice, owing in large part to its ability to penetrate the cell membrane and reduce intracellular ice formation and osmotic stress during freezing and thawing. However, while effective and ubiquitous, DMSO has also not been free of controversy: it has been described as not inert, able to induce epigenetic changes in immune cells, 12 and its use has been associated with mild-tosevere side effects in patients receiving cell therapy infusions, 13−15 with direct effects on NK cell function having been reported due to its use.…”
Section: ■ Introductionmentioning
confidence: 99%